Biochar-Soil-Plant interactions: A cross talk for sustainable agriculture under changing climate - Murtaza, Ghulam; Ahmed, Zeeshan; Eldin, Sayed M.; Ali, Basharat; Bawazeer, Sami; Usman, Muhammad; Iqbal, Rashid; Neupane, Dhurba; Ullah, Abd; Khan, Ahmad; Hassan, Muhammad Umair; Ali, Iftikhar; et al. (Frontiers in Environmental Science, 2023)
Biochars provide several agricultural and environmental benefits, such as soil health improvement, better crop growth and yield, carbon sequestration, decreasing greenhouse gas (GHGs) emissions, and regulation of nutrient dynamics. This review highlights the role of biochar in transforming the soil's physiochemical and biological properties, and their impact on improving seed germination and seedling growth, altering crop physiological attributes, enhancing crop resistance against biotic and abiotic stresses, improving crop productivity, curtailing GHGs, and controlling nutrient leaching losses. However, the type of feedstock used, pyrolysis temperature, application rate and method, soil type and crop species largely influence the biochar performance under different environmental conditions. Application of biochars at low rates help to promote seed germination and seedling growth. Biochar modified the abiotic and microbial processes in the rhizosphere and increased nutrient mineralization and enhanced the nutrient availability for plant uptake. Hence, biochar enhanced the plant resistance against diseases, reduced the availability of heavy metals and improved the plant resilience against environmental stressors. By providing a comprehensive analysis about the variable impacts of biochars on soil physicochemical properties, plant growth, development and productivity and mitigating environmental problems, this review is quite valuable for developing an efficient soil and crop specific biochar with desired functionalities. It could be helpful in improving crop productivity, ensuring food security and better management of environment. Furthermore, this review identifies the knowledge gaps and suggests future outlooks for the commercialization of biochar applications on large-scale.